2009
DOI: 10.1128/aem.02683-08
|View full text |Cite
|
Sign up to set email alerts
|

Organoselenium Coating on Cellulose Inhibits the Formation of Biofilms byPseudomonas aeruginosaandStaphylococcus aureus

Abstract: Among the most difficult bacterial infections encountered in treating patients are wound infections, which may occur in burn victims, patients with traumatic wounds, necrotic lesions in people with diabetes, and patients with surgical wounds. Within a wound, infecting bacteria frequently develop biofilms. Many current wound dressings are impregnated with antimicrobial agents, such as silver or antibiotics. Diffusion of the agent(s) from the dressing may damage or destroy nearby healthy tissue as well as compro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
86
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(91 citation statements)
references
References 51 publications
2
86
0
2
Order By: Relevance
“…In particular, antimicrobial effects of different selenium compounds have been attributed to the formation of free radicals (Tran et al ., 2009). In this study, exposure of three bacterial strains (namely P .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, antimicrobial effects of different selenium compounds have been attributed to the formation of free radicals (Tran et al ., 2009). In this study, exposure of three bacterial strains (namely P .…”
Section: Discussionmentioning
confidence: 99%
“…Also, we have shown, in a previous study, that organo-selenium in polymer form can generate superoxide radicals (Tran et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The superoxide radical appears to account for most of selenium's toxicity toward different bacteria, such as Staphylococcus epidermidis, Staphylococcus aureus, Listeria monocytogenes, Salmonella typhimurium, and Escherichia coli in vitro (Babior et al, 1975;Bortolussi et al, 1987;Kramer and Ames, 1988). We previously showed that organo-selenium covalently attached to different biomaterials and medical devices, such as intravenous catheter, contact lenses, and reverse osmosis (RO) membranes, as well as cellulose, blocks the formation of Staphylococcus aureus and Pseudomonas aeruginosa biofilms (Mathews et al, 2006;Tran et al, 2009Tran et al, , 2012Reid et al, 2010;Low et al, 2011). Low concentrations of organo-selenium (0.1% or 0.2%) were sufficient to inhibit bacterial attachment to these materials.…”
mentioning
confidence: 99%
“…15,16 Others reported inhibitory effects of selenium compounds (in the form of coatings) on the growth of some types of bacteria. 17 However, the influence of selenium nanoparticles on bacteria growth remains largely unexplored. …”
Section: Discussionmentioning
confidence: 99%